2018
DOI: 10.1155/2018/5205642
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind after Severe Acquired Brain Injury: Clues for Interpretation

Abstract: Background. Recently, increased interest has been shown in Theory of Mind (ToM) abilities of individuals with severe acquired brain injury (sABI). ToM impairment following sABI can be associated with altered executive functioning and/or with difficulty in decoding and elaborating emotions. Two main theoretical models have been proposed to explain the mechanisms underlying ToM in the general population: Theory Theory and Simulation Theory. This review presents and discusses the literature on ToM abilities in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Neurobehavioral disability has also been described in nontraumatic acquired brain injuries (nt-ABI). Indeed, several behavioral changes have been described among these latter patients (16), including disorders of social perceptiveness, self-control and/or emotional regulation, decreased ability to learn from social experience, difficulties with impulse control, development of sociopathic or borderline traits, loss of self-sense, childish behavior, disinhibited behavior, and poor social judgment (17). Thus, non-cognitive behavioral impairments may be considered a landmark of ABI regardless of its etiology.…”
Section: Introductionmentioning
confidence: 99%
“…Neurobehavioral disability has also been described in nontraumatic acquired brain injuries (nt-ABI). Indeed, several behavioral changes have been described among these latter patients (16), including disorders of social perceptiveness, self-control and/or emotional regulation, decreased ability to learn from social experience, difficulties with impulse control, development of sociopathic or borderline traits, loss of self-sense, childish behavior, disinhibited behavior, and poor social judgment (17). Thus, non-cognitive behavioral impairments may be considered a landmark of ABI regardless of its etiology.…”
Section: Introductionmentioning
confidence: 99%
“…The Simulation Theory also has support from studies reporting associations between low self-awareness, emotional disturbances and low ToM scores (Bivona et al, 2014;de Sousa, McDonald, Rushby, Dimoska & James, 2010). Bivona et al, (2018) concluded that the two models are more than likely not mutually exclusive in explaining ToM and mentalizing impairments post-TBI and more research is needed in the area to fully understand these univocal findings.…”
Section: Multifaceted Components Of Social Cognition Post-tbimentioning
confidence: 98%
“…In a recent review by Bivona et al, (2018), the authors outlined the two main theoretical models explaining ToM. 'Theory Theory' suggests that humans infer other people's intentions and beliefs by deploying general principles, such as cultural rules and laws, with the involvement of executive functions, abstract reasoning and working memory (Carruthers & Smith, 1996).…”
Section: Multifaceted Components Of Social Cognition Post-tbimentioning
confidence: 99%